ON pathway mutations increase susceptibility to form-deprivation myopia. (August 2015) - Chakraborty, Ranjay; Park, Han na; Hanif, Adam M.; Sidhu, Curran S.; Iuvone, P. Michael; Pardue, Machelle T.
Abstract: The ON pathway mutation in nob mice is associated with altered refractive development, and an increased susceptibility to form-deprivation (FD) myopia. In this study, we used mGluR6-/- mice, another ON pathway mutant, to determine whether the nob phenotype was due to the Nyx mutation or abnormal ON pathway transmission. Refractive development under a normal visual environment for mGluR6-/- and age-matched wild-type (WT) mice was measured every 2 weeks from 4 to 16 weeks of age. The response to monocular FD from 4 weeks of age was measured weekly in a separate cohort of mice. Refraction and ocular biometry were obtained using a photorefractor and optical coherence tomography. Retinas were harvested at 16 weeks, and analyzed for dopamine (DA) and DOPAC using high-performance liquid chromatography. Under normal conditions, mGluR6-/- mice were significantly more myopic than their WT controls (refraction at 12 weeks; WT: 9.40 ± 0.16 D, mGluR6-/- : 6.91 ± 0.38 D). Similar to nob mice, two weeks of FD resulted in a significant myopic shift of −5.57 ± 0.72 D in mGluR6-/- mice compared to −1.66 ± 0.19 D in WT animals. No significant axial length changes were observed with either normal or FD visual conditions. At 16 weeks, mGluR6-/- retinas showed significantly lower DOPAC levels (111.2 ± 33.0 pg/mg) compared to their WT counterparts (197.5 ± 11.2 pg/mg). Retinal DA levels were similar between the different genotypes. Our results indicate that reduced retinal DA metabolism/turnover may be associated with increased susceptibility to myopia in mice with ON pathway defect mutations. Highlights: Functional mGluR6 receptor is important for normal refractive development in mice. mGluR6 mutation leads to myopic eye growth in mice. mGluR6 mutation increases the susceptibility to form-deprivation myopia in mice. Reduced retinal dopamine may cause increased myopia susceptibility in mGluR6 mutant. Both nob and mGluR6 ON pathway mutants exhibit similar refractive phenotypes.